Sense of school belonging: A strategy for institutional and academic strengthening - Castañeda Burciaga, Selene; Ramírez Salazar, Martha Angélica; Guirette-Barbosa, Omar A. (IE Revista de Investigación Educativa de la REDIECH, 2025)
The current educational demand forces institutions to implement various strategies focused not only on attracting students but also on fostering their sense of identity, which can transcend in their permanence. The objective of this research is to identify the level of sense of belonging of the students of a private university, through the analysis of the factors that intervene in it. A cross-sectional, descriptive and non-experimental study was carried out with a sample of 320 students, to whom the perception of sense of belonging scale was applied. The main results show that, for the most part, students have a high sense of belonging to the university; furthermore, it is observed that, derived from a correlational analysis, the aspects with the highest relationship with the sense of belonging are age, educational level, occupation and academic average. As limitations, the size of the sample is identified, therefore, it is suggested to expand the population and replicate the study in different academic contexts. The originality of the work is recognized in the identification of strategies that allow to recruit students and also foster their sense of belonging.